Applications of nanofluids in chemical and bio-medical process industry - Sonawane, Shriram S.; Mohammed, Hussein A.; Mungray, Arvind Kumar; Sonawane, Shirish Hari (Elsevier, 2022)
Applications of Nanofluids in the Chemical and Biomedical Process Industry provides detailed knowledge about the mathematical, numerical, and experimental methodologies of the application of nanofluids in heat transfer, mass transfer, and biomedical processes. The book is divided into three main sections with the first providing a detailed overview of the thermophysical and optical properties of nanofluids enhancement in heat exchangers and boiling operations. The second section gives a detailed overview of nanofluid application in CO2 absorption/regeneration and metal extraction/stripping operations, while the third provides an overview of the application ofnanofluids in biomedical processes. The book includes recent advances, as well as challenges to nanofluid applications in industrial processes and will be useful for researchers and professionals working in industry or academia, as well as others interested in the applications of the nanofluids to industrial processes for design purposes.